Inhibition of p53 protein aggregation as a cancer treatment strategy. (February 2023) - Kwan, Kalvin; Castro-Sandoval, Omar; Gaiddon, Christian; Storr, Tim
Abstract: The p53 protein plays a critical role in the prevention of genome mutations in the body, however, this protein is frequently mutated in cancer and almost all cancers exhibit malfunction along the p53 pathway. In addition to a loss of activity, mutant p53 protein is prone to unfolding and aggregation, eventually forming amyloid aggregates. There continues to be a considerable effort to develop strategies to restore normal p53 expression and activity and this review details recent advances in small-molecule stabilization of mutant p53 protein and the design of p53 aggregation inhibitors.